The clinical application of flexible bronchoscopy in a neonatal intensive care unit - Ke, Li-qin; Shi, Ming-jie; Zhang, Fei-zhou; Wu, Hu-jun; Wu, Lei; Tang, Lan-fang (Frontiers in Pediatrics, 2022)
Objective Flexible bronchoscopy is widely used in infants and it plays a crucial role. The aim of this study was to investigate the value and clinical safety of flexible bronchoscopy in a neonatal intensive care unit. Methods A retrospective analysis was performed on the clinical data of 116 neonates who underwent flexible bronchoscopy and the outcomes of 147 procedures. A correlation analysis was performed on the relationship between flexible bronchoscopy findings, microscopic indications, and clinical disease. Results The 147 procedures performed were due to the following reasons: problems related to artificial airways, 58 cases (39.45%); upper respiratory problems, 60 cases (40.81%) (recurrent dyspnea, 23 cases; upper airway obstruction, 17 cases; recurrent stridor, 14 cases; and hoarseness, six cases), lower respiratory problems, 51 cases (34.69%) (persistent pneumonia, 21 cases; suspicious airway anatomical disease, 21 cases; recurrent atelectasis, eight cases; and pneumorrhagia, one case), feeding difficulty three cases (2.04%). The 147 endoscopic examinations were performed for the following reasons: pathological changes, 141 cases (95.92%); laryngomalacia, 78 cases (53.06%); mucosal inflammation/secretions, 64 cases (43.54%); vocal cord paralysis, 29 cases (19.72%); trachea/bronchus stenosis, 17 cases (11.56%) [five cases of congenital annular constriction of the trachea, seven cases of left main tracheal stenosis, one case of the right middle bronchial stenosis, two cases of tracheal compression, and two cases of congenital tracheal stenosis]; subglottic lesions, 15 cases (10.20%) [eight cases of subglottic granulation tissue, six cases of subglottic stenosis, one cases of subglottic hemangioma]; tracheomalacia, 14 cases (9.52%); laryngeal edema, five cases (3.40%); tracheoesophageal fistula, four cases (2.72%); rhinostenosis, three cases (2.04%); tracheal bronchus, three cases (2.04%); glossoptosis, two cases (1.36%); laryngeal cyst, two cases (1.36%); laryngeal cleft, two cases (1.36%); tongue base cysts, one case (0.68%); and pneumorrhagia, one case (0.68%). Complications were rare and mild. Conclusion Flexible bronchoscopy is safe and effective for diagnosing and differentiating neonatal respiratory disorders in neonatal intensive care units.